Failure of BACTEC™ MGIT 960™ to detect Mycobacterium tuberculosis complex within a 42-day incubation period - Sharana Mahomed; Nomonde R. Dlamini-Mvelase; Moses Dlamini; Koleka Mlisana (AOSIS, 2017)
For the optimal recovery of Mycobacterium tuberculosis from the BACTEC™ Mycobacterium Growth Indicator Tube 960™ system, an incubation period of 42-56 days is recommended by the manufacturer. Due to logistical reasons, it is common practice to follow an incubation period of 42 days. We undertook a retrospective study to document positive Mycobacterium Growth Indicator Tube cultures beyond the 42-day incubation period. In total, 98/110 (89%) were positive for M. tuberculosis complex. This alerted us to M. tuberculosis growth detection failure at 42 days.